THE EFFECT OF LANGUAGE ANXIETY IN THE CLASSROOM - Ana Fergina (Guru Membangun, 2010)
This study aims to investigate factors contributing to anxiety. The study attempts to investigate whether language anxiety gives positive or negative impacts to language learners. It also tries to see how different educational system influences learners belief in learning a language. The findings indicate that the subject experienced anxiety in classroom particularly when she was asked to do oral presentation in the classroom. This was because she grew up in different language background and educational system. Although the subject was anxious when speaking in from of the class, she could manage her anxiety by preparing the presentation well.